1996
DOI: 10.2307/3870209
|View full text |Cite
|
Sign up to set email alerts
|

The Miniature1 Seed Locus of Maize Encodes a Cell Wall Invertase Required for Normal Development of Endosperm and Maternal Cells in the Pedicel

Abstract: Collective evidence demonstrates that the Miniature1 (Mn1) seed locus in maize encodes an endosperm-specific isozyme of cell wall Invertase, CWI-2. The evidence includes (1) isolation and characterization of ethyl methanesulfonate-induced mn1 mutants with altered enzyme activity and (2) a near-linear relationship between gene/dose and invertase activity and the CWI-2 protein. In addition, molecular analyses showed that the cDNA clone incw2 maps to the Mn1 locus and differentiates the six ethyl methanesulfonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
197
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(221 citation statements)
references
References 0 publications
19
197
1
1
Order By: Relevance
“…With an exception in tobacco (Nicotiana tabacum; Tomlinson et al, 2004), high and low Glc-to-Suc ratios generally favor cell division or promote cell differentiation, respectively, during seed development (for review, see Weber et al, 2005). Consistently, high CWIN activities correlate with high Glc level and mitotic activity in faba bean embryo (Weber et al, 1996(Weber et al, , 1997 and maize endosperm (Cheng et al, 1996;Vilhar et al, 2002). Loss of CWIN expression reduces seed filling in maize (Cheng et al, 1996) and rice , whereas elevation of CWIN activity by silencing its inhibitor increases seed size in tomato (Jin et al, 2009), demonstrating the critical role of CWIN in seed development.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…With an exception in tobacco (Nicotiana tabacum; Tomlinson et al, 2004), high and low Glc-to-Suc ratios generally favor cell division or promote cell differentiation, respectively, during seed development (for review, see Weber et al, 2005). Consistently, high CWIN activities correlate with high Glc level and mitotic activity in faba bean embryo (Weber et al, 1996(Weber et al, , 1997 and maize endosperm (Cheng et al, 1996;Vilhar et al, 2002). Loss of CWIN expression reduces seed filling in maize (Cheng et al, 1996) and rice , whereas elevation of CWIN activity by silencing its inhibitor increases seed size in tomato (Jin et al, 2009), demonstrating the critical role of CWIN in seed development.…”
mentioning
confidence: 64%
“…Extensive studies have shown essential roles of CWIN in seed filling, probably through regulating Suc unloading and the establishment and maintenance of sink strength (Cheng et al, 1996;Weber et al, 1996;Wang et al, 2008;Jin et al, 2009;Zanor et al, 2009). However, it remains largely unknown how CWIN exerts its regulation early in seed development .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 14 genes have one eQTL and 2 genes have two eQTLs. The mn1 gene, which encodes an endospermspecific cell wall invertase and determines the kernel size 26 , is predicted to be regulated by a gene encoding the UDP-glycosyl transferase ( Supplementary Fig. S16).…”
Section: Articlementioning
confidence: 99%